Konsep Keadilan dalam Sistem Peradilan Perdata - Elisabeth Nurhaini Butarbutar (Fakultas Hukum Universitas Gadjah Mada, 2009)
Conflict on civil matters is an absolute competency of District Court. Judiciary system includes all items in relating with a judge assignment giving justice to the justiciable through the conviction. A court judges according to law and should not make discrimination. The provision becomes a principle for civil judge to process the conflict matter which is submitted on him/her. The justice concept on the civil judiciary system is a justice which is given by a judge during the judiciary on civil conflict, to produce a conviction. In the conflict of civil matter, it known as audi et alteram partem and to each his own principle. Audi et alteram partem principle. It means that giving to that every person on conflict should be equally treated. To each his own principle, it means that every person take everything as his own. In implementation, it look both of principles is contradiction each other. Because in the law system should not have any conflict, so both of the principle should be exist in the the conflict of civil matters.